Pengukuran Efektivitas Mesin Menggunakan Overall Equipment Effectiveness Untuk Dasar Usulan Perbaikan - Bernandus Yoseph Bilianto; Yurida Ekawati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
CV. Gracia has offset printing machines that often have downtime due to engine failures. The low effectiveness of the offset printing machines could cause losses to the company. Overall Equipment Effectiveness (OEE) method is a tool to determine the success rate of Total Productive Maintenance (TPM) based on categories of availability, performance, and quality. The OEE average value of the company in 2014, 57%, is relatively low. In this study, causes of this low OEE is analyzed using Failure Mode and Effect Analysis (FMEA) and fishbone diagram. Improvements such as relocation of raw material and colourful catalog were subsequently proposed and implemented during April - May 2016. The implementation resulted in OEE average value of 60%.